Temperature effects on mechanical response and failure mechanism of 3D angle-interlock woven carbon/epoxy composites. (April 2020) - Dang, Ming-guang; Li, Dian-sen; Jiang, Lei
Abstract: This paper reveals the fabrication of 3D angle-interlock woven carbon/epoxy composites and reports the temperature effects on their mechanical behavior and failure mechanism. The results show the temperature has a significant influence on the bending properties and failure mechanism of 3D angle-interlock woven composite. The load/deflection curves are linear elasticity, while at high temperatures showing obvious nonlinear feature and long plasticity plateau. Moreover, bending properties gradually decrease with increasing the temperature, and when the temperature exceeds 150 °C, the decrement accelerates. Macro-fracture morphology and SEM fractographs show that microcrack generation and transmission on the compression surface, fiber/matrix interface debonding, and fibers breakage are the main failure mechanisms of materials at room temperature. With increasing the temperature, the materials become more softened and achieve plasticity. The fibers breakage, matrix yielding and cracking, and interface debonding become distinguished. Highlights: High temperature mechanical responses of 3D angle-interlock woven carbon/epoxy composites are obtained. High temperature bending failure mechanisms of 3D angle-interlock woven carbon/epoxy composites are demonstrated. The influences of temperature on mechanical responses and failure mechanisms are analyzed.